Augmented environments for computer-assisted interventions : 10th International Workshop, AE-CAI 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 9, 2015. Proceedings /: 10th International Workshop, AE-CAI 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 9, 2015. Proceedings. (2015) - Unknown
No abstract available